Relationship between Family Income and Stunting Incidence in Kebun Kelapa Village, Secanggang District - Srinur Nilawati (Institute of Computer Science (IOCS), 2022)
WHO states that stunting is a condition of failure to grow and develop in children which can be seen from the height that is not in accordance with their age. Growth failure that occurs in stunted children is caused by several factors such as poverty, lack of awareness of health, malnutrition and poo parenting styles. The consequences of stunting are a decrease in the level of intelligence and children will easily contract a disease. This type of research is descriptive analysis with a cross sectional research design to determine the relationship between family income and the incidence of stunting in Kebun Kelapa Village. The subjects of this study werw 26 families with stunting children aged 0-59 months. The results showed that there was a relationship between family income and the incidence of stunting in Kebun Kelapa Village, Secanggang District.